Prognostic role of angiotensin-II receptor type 1 and endothelin-1 receptor type A agonistic autoantibodies in patients with acute myocardial infarction - Tona, Francesco; Civieri, Giovanni; Vadori, Marta; Masiero, Giulia; Iop, Laura; Perazzolo Marra, Martina; Cecere, Annagrazia; Martini, Marika; Tansella, Donatella; Bernava, Giacomo; Schiavon, Benedetta; Leoni, Loira; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFunctional autoantibodies against angiotensin II type 1 (AT1R-AAs) and endothelin-1 type A (ETAR-AAs) receptors are associated with microvascular obstruction and myocardial remodeling after ST-elevation myocardial infarction (STEMI). However, their role in the long-term prognosis after STEMI has not been investigated.MethodsThis is a prospective observational study enrolling STEMI patients undergoing early primary PCI. The incidence of major adverse cardiovascular events (MACE) was investigated during the follow-up. Autoantibody seropositivity was defined as a level >10 U/ml.Results200 STEMI patients (89% male, median age 61 years) were enrolled. 110 (55%) were seronegative for both autoantibodies, 44 (22%) were seropositive for one autoantibody, and 46 (23%) were seropositive for both autoantibodies. Over a median follow-up of 1.2 years, the incidence of MACE was higher in patients with double (31%) and single (25%) seropositivity than in seronegative patients (13%, p = 0.02 among groups). Double seropositivity was independently associated with higher risk of MACE (HR 2.386, 95% CI 1.471–3.864, p < 0.001).ConclusionAT1R-AAs and ETAR-AAs are associated with an increased risk of MACE after STEMI. Assessment of autoantibody levels paves the way for future therapies targeting specific molecular pathways associated with poor prognosis after an acute coronary event.